Estimating the Skill Bias in Agglomeration Externalities and Social Returns to Education: Evidence from Dutch Matched Worker-Firm Micro-data - Stefan P.T. Groot; Henri L.F. de Groot (Tinbergen Institute, 2014)
This paper employs a unique set of micro-data covering almost one third of the Dutch labor force, to estimate the relationship between agglomeration externalities and the level of education. While the positive relationship between economic density and productivity and wages has long been established in the economic literature, less is known about the effects of density on the productivity of different types of workers. This paper shows that there is substantial heterogeneity in the relationship between density and productivity for workers with different types of education. Apart from estimating the impact of aggregate density, we also estimate whether the composition of the local labor market in terms of education is related to the productivity of different types of workers. Using the presence of universities as an instrument, we estimate the effect of the supply of university graduates on wages, i.e. the social return to education.
Keywords: J03; I02; 330; agglomeration; education; knowledge-spillovers; wages; local labor markets